High prevalence of soil-transmitted helminth infections in Myanmar schoolchildren - Eindra Aung; Kay Thwe Han; Catherine A. Gordon; Nyein Nyein Hlaing; Moe Moe Aye; Myo Win Htun; Khin Thet Wai; Su Mon Myat; Thida Lay Thwe; Aung Tun; Kinley Wangdi; Yuesheng Li; et al. (BMC, 2022)
Abstract Background Achieving the elimination of soil-transmitted helminth (STH) infections requires a sufficient understanding of the current epidemiological status of STH endemicity. We aimed to examine the status of STH in Myanmar - a country with the eighth highest STH prevalence in the world, 10 years after instigation of the national deworming programme. Methods In August 2016 we screened for STH infections using Kato Katz (KK) microscopy and real-time PCR (qPCR) in schoolchildren from the Bago Region township of Phyu, a STH sentinel site in Myanmar. Ten schools were randomly selected, and one stool sample each from a total of 264 students was examined. Prevalence and intensity of infection were calculated for each STH. Results High prevalence of STH was identified in the study area with 78.8% of the schoolchildren infected with at least one STH by qPCR, and 33.3% by KK. The most prevalent STH was Trichuris trichiura, diagnosed by both KK (26.1%) and qPCR (67.1%), followed by Ascaris lumbricoides (15.5% KK; 54.9% qPCR). No hookworm infections were identified by KK; however, the qPCR analysis showed a high prevalence of Ancylostoma sp. infection (29.6%) with few Necator americanus (1.1%) infections. Conclusions Despite bi-annual deworming of schoolchildren in the fourth-grade and below, STH prevalence remains stubbornly high. These results informed the expansion of the Myanmar National STH control programme to include all school-aged children by the Ministry of Health and Sports in 2017, however further expansion to the whole community should be considered along with improving sanitation and hygiene measures. This would be augmented by rigorous monitoring and evaluation, including national prevalence surveys.